ESP Need Analysis: An Analysis of English Language Needs for Administrative Tasks in Health Administration Program - Nurul Faradillah; Sam Hermansyah; Nur Hikmah; Isumarni; Sitti Aisa (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
English proficiency is increasingly important in health administration, particularly for supporting administrative tasks such as documentation, correspondence, reporting, scheduling, and professional coordination. However, English instruction in health administration programs often focuses on General English rather than the specific language needs required in healthcare administrative contexts. This study aimed to analyze the English language needs and difficulties of fifth-semester students in the Health Administration Program at Universitas Muhammadiyah Sidenreng Rappang in relation to administrative tasks. This research employed a descriptive quantitative design. Data were collected through a structured questionnaire using a Likert-scale format, covering four English language skills: reading, writing, listening, and speaking. The participants consisted of six fifth-semester students, and the data were analyzed using descriptive statistics in the form of frequencies and percentages. The findings showed that students generally expressed neutral perceptions regarding both their English language needs and difficulties across the four skills. This indicates limited exposure to authentic administrative tasks requiring English use. Nevertheless, reading and writing were perceived as relatively more relevant, especially for understanding administrative documents, written procedures, reports, and formal correspondence. Writing tasks also showed slightly higher indications of difficulty compared to other skills. These findings suggest that English for Specific Purposes instruction in health administration should be more context-based and aligned with real administrative tasks to better prepare students for future professional roles.